Factors influencing working conditions of small enterprises in Sylhet City, Bangladesh. Issue 1 (2nd January 2018) - Hussain, A.H.M. Belayeth; Endut, Noraida
ABSTRACT: This article looks at variables that affect the working lives of small business entrepreneurs in Sylhet City, Bangladesh, and whether microfinance ensures decent working conditions in small ventures. The findings show that social dialogue among borrowers and their enterprise stability have the largest impacts on work and non-work life, and that social discussions among borrowers have the most significance in achieving harmony between work and non-work life. The results suggest that loan organisations need to draw in their borrowers more by using social relations in empowering decent working conditions.